Prevalence and associated factors of diabetes mellitus among tuberculosis patients in Brunei Darussalam: A 6-year retrospective cohort study. (April 2021) - Omar, Nurfakhrina; Wong, Justin; Thu, Kyaw; Alikhan, Md Fathi; Chaw, Liling
Highlights: This is a retrospective study of all TB patients in Brunei from 2013 to 2018. About one-third of all tuberculosis (TB) cases were also diagnosed with diabetes mellitus (DM). Incidence of newly diagnosed DM among TB patients was 74.2 per 1000 people. Associated factors were older age, smear-positive TB, and other comorbidities. Bidirectional screening can facilitate early detection and treatment of TB and DM. Abstract: Objectives: To determine the prevalence and associated factors of diabetes mellitus (DM) among tuberculosis (TB) cases in Brunei Darussalam. Methods: We conducted a retrospective cohort study among all TB patients registered between 2013 and 2018. Collected data include sociodemographics, comorbidities, and information related to their TB diagnosis and treatment outcomes. Associated factors of having DM among TB patients were investigated using logistic regression analyses. Results: We identified a total of 1362 TB patients, among which 462 (33.9% [95%CI: 31.4%, 36.5%]) also have DM. 70.6% (n = 326) were diagnosed with DM at least six months prior to their TB diagnosis. The incidence of newly diagnosed DM among TB patients was 74.2 per 1000 population. Significant factors of having TB and DM comorbidity were age (adjusted OR (adj. OR) = 1.04 [95%CI: 10.3, 1.05]), classified as smear-positive pulmonary TB (adj. OR = 5.77 [95%CI: 3.71, 9.22]), having the following underlying conditions: hypertension/heart disease (adj. OR = 24.05 [95%CI: 5.80, 100.05]), renal disease (adj. OR = 7.34 [95%CI: 2.88, 20.22]) and chronic obstructive pulmonary disease/asthma (adj. OR = 0.38 [95%CI: 0.22, 0.64]). Conclusion: About one-third of TB cases in Brunei were also diagnosed with DM. Bi-directional screening could be a good strategy to facilitate early detection and treatment of both diseases.